"It's In My Veins": Exploring the Role of an Afrocentric, Popular Education-Based Training Program in the Empowerment of African American and African Community Health Workers in Oregon. Issue 4 (October 2015) - Bridgeman-Bunyoli, Arika; Mitchell, S. Renee; bin Abdullah, Abdul'Hafeedh M.; Schwoeffermann, Ty; Phoenix, Toliver; Goughnour, Cat; Hines-Norwood, Richard; Wiggins, Noelle
Abstract : The role racism and other social determinants of health play in the creation of health inequities in African American communities in the United States is increasingly understood. In this article, we explore the effectiveness of an Afrocentric, popular education–based community health worker (CHW) training program in creating positive change among CHW participants and their communities in Portland, Oregon. Findings suggest that CHW participants experienced 4 types of awakening, in addition to changes in their interaction with their family members and increased community involvement. The CHWs identified group bond, Afrocentrism, public health knowledge, popular education, facilitators, and time management as important elements of an effective training program for this community. Psychological empowerment, self-reported health status, and health behavior among participants generally increased over time, but changes were not statistically significant. Abstract : Supplemental Digital Content is Available in the Text.